Staging deaths: King Sverre or a usurper’s path to the throne - Brégaint, David (2018)
The present study explores how the Norwegian usurper, King Sverre (1184-1202) exploited three princely burials to overthrow the ruling king and establish his dynasty. Both in 1179 and 1184, King Sverre took full advantage of his military victories to gain popular support for his claims to the throne, in transforming the burial of his most prominent enemies felt on the battlefield into a rostrum for his political propaganda, through speeches and ritual staging. Sverre’s own agony and funerals were also meticulously staged in order to defend his rule from accusations of excommunication and pave the way for his succession. The study provides insights on the challenges met by a usurper on his way to royal power and, in particular, on the concomitant relationship between military combat and the work of political persuasion.   Bibliography Printed sources NORGES GAMLE Love indtil 1387. Ed. R. Keyser and P.A. Münch: Kristiania, 1846-1895. SNORRE STURLASON – Saga of Magnus Erlingsson. Ed. Samuel Laing. Heimskringla: A history of the Norse kings. London: Norroena Society, 1907. THE SAGA of King Sverri of Norway. Ed. J. Sephton. Somerset: Llanerch Press, 1899. JÓNSSON, Karl – Sverris saga. Ed. Gustav Indrebø, Historiske Kildeskriftkommission. Münch: Kristiania, 1920.   Studies BAGGE, Sverre – From gang leader to the Lord’s anointed. Kingship in Sverris saga and Hákonar saga Hákonarsonar. Odense, Denmark: Odense University Press, 1996. – From Viking Stronghold to Christian Kingdom, Museum Tusculanum Press, 2010. BLÖNDAL, Lárus – Um uppruna Sverrissögu. Reykjavík: Stofnun Árna Magnússonar, 1982. BRÉGAINT, David – Vox regis. Royal communication in High Medieval Norway. Leiden: Brill, 2016. ELLUL, Jacques – Propaganda. The Formation of Men’s Attitudes. London: Vintage Books Edition, 1973 (1965). GUNNES, Erik – Kongens Ære. Kongemakt og kirke i “En Tale mot biskopene”. Norge: Gyldendal Norsk Forlag, 1971. HOLM-OLSEN, L. – “Sverris saga”. in OLSEN, O. et alii (ed.) – Kultur historisk leksikon for nordisk middelalder fra vikingetid til reformasjonstid. København: Rosenkilde og Bagger 1978, Vol. XVII, pp. 551-558. KNIRK, James E. – Oratory in the King’s sagas. Oslo: Universitetsforlaget, 1981. KRAG, Claus – Norges historie fram til 1319. Oslo: Universitetsforlaget, 2000. – Sverre. Norges største middelalderkonge. Oslo: Aschehoug, 2005. – “Sverre vinner kongedømmet”. in OLSEN, Per E. (red.) – Norges kriger. Fra Hafrsfjord til Afghanistan. Norge: Vega Forlag, 2011, pp. 104-109. OLSEN, O. et alii (ed.) – Kultur Historisk Leksikon for Nordisk Middelalder fra vikingetid til reformasjonstid. København: Rosenkilde og Bagger 1978.